The information economy, industry and market in 2013 - Baiget, Tomí s; Olea, Isabel (Anuario ThinkEPI, 2014)
Characteristics and economic data of the information market come from various sources and are somewhat mixed. Specific aspects and products discussed are the valuation of the global information market, corporate acquisitions, major scientific publishers, publishing markets (countries), cost of WoK and Scopus databases, revaluation of economic information since the 2008 crisis, journal price increases, open access market, evolution of computing costs (Moore´s Law) and major vendors.